Histone modifications and chromatin remodelling in plants in response to salt stress. Issue 4 (2nd June 2021) - Yung, Wai‐Shing; Li, Man‐Wah; Sze, Ching‐Ching; Wang, Qianwen; Lam, Hon‐Ming
Abstract: In the face of global food security crises, it is necessary to boost agricultural production. One factor hampering the attempts to increase food production is elevated soil salinity, which can be due to salt that is naturally present in the soil or a consequence of excessive or prolonged irrigation or application of fertiliser. In response to environmental stresses, plants activate multiple molecular mechanisms, including the timely activation of stress‐responsive transcriptional networks. However, in the case of salt stress, the combined effects of the initial osmotic shock and the subsequent ion‐specific stress increase the complexity in the selective regulation of gene expressions involved in restoring or maintaining osmotic balance, ion homeostasis and reactive oxygen species scavenging. Histone modifications and chromatin remodelling are important epigenetic processes that regulate gene expressions by modifying the chromatin status and recruiting transcription regulators. In this review, we have specifically summarised the currently available knowledge on histone modifications and chromatin remodelling in relation to plant responses to salt stress. Current findings have revealed the functional importance of chromatin modifiers in regulating salt tolerance and identified the effector genes affected by epigenetic modifications, although counteraction between modifiers within the same family may occur. Emerging evidence has also illustrated the crosstalk between epigenetic modifications and hormone signalling pathways which involves formation of protein complexes. With an improved understanding of these processes, plant breeders will be able to develop alternative strategies using genome editing technologies for crop improvement.